Miles to go for freedom : segregation & civil rights in the Jim Crow years - Osborne, Linda Barrett, 1949- (Abrams Books for Young Readers, 2012)
Describes the lives of African Americans during the Jim Crow years, a period of legal segregation and discrimination from the 1890s through the 1950s, including photographs and interviews with African Americans who were young during this time and other primary resources.